(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
Clothing has always been the most prominent cultural element that reflects the identity of peoples. Thus, It represents a key practice deeply rooted in the collective social memory, distinguished between social classes and drawn between urban and rural lifestyles. In this light, the current article highlights the most distinctive garments of Algerian culture and their socio-historical development, illustrating their continued presence in daily life and the ease with which they are being reproduced in light of the challenges posed by modernity.